P-009 Natural history, angiographic presentation and outcomes of anterior cranial fossa dural arteriovenous fistulas. (23rd July 2022) - Sanchez, S; Raghuram, A; Wendt, L; Hayakawa, M; Chen, C; Sheehan, J; Kim, L; Abecassis, I; Levitt, M; Jayaraman, K; Guniganti, R; Kansagra, A; et al.
Abstract : Introduction: Anterior cranial fossa dural arteriovenous fistulas (ACF-dAVFs) have a high risk of rupture. The most important determinant of symptoms and risk of hemorrhage is the pattern of venous drainage. The absence of major venous sinuses in the anterior cranial fossa leads to drainage through delicate small cortical veins that can easily bleed. We present a comprehensive analysis of natural history, angiographic presentation, and outcomes of a large cohort of ACF-dAVFs from the CONDOR database. Method: The CONDOR consortium is a repository that contains data from 1077 dural arteriovenous fistulas (dAVF) diagnosed in 12 international centers. The consortium includes patients that were diagnosed with dAVFs from 1990 to 2017. dAVFs were classified into various groups depending on the anatomical location. Data from ACF-dAVFs was analyzed from the CONDOR repository. Results: A total of 60 ACF-dAVFs were included. The mean age was 61±12 and 63% (38/60) were male. Sixty-three percent (38/60) of ACF-dAVF had a symptomatic presentation. Intracranial hemorrhage was the most common presentation 58% (22/38). The ethmoidal artery was the most common arterial feeder (66%, 40/60). Instead of draining directly to a sinus, most ACF-dAVFs (93%, 56/60) drained through cortical veins. Drainage through small cortical veins predicted symptomatic onset (OR 9.42, CI 1.98–69.1, p=0.01) ( table 1 ). Ultimately, most ACF-dAVFs with cortical venous drainage, drained into the superior sagittal sinus (60%, 34/56). Signs of venous ectasia were present in 53% (32/60) of patients. Eighty-eight percent (53/60) of ACF-dAVFs were treated. Microsurgery was the most successful modality of treatment achieving fistula closure in all cases (n=35). Obliteration of the ACF-dAVF was achieved in 53% (9/17) of endovascular interventions. Radiosurgery was attempted without success in one patient. None of the untreated patients had improvement of symptoms and 57% (4/7) had worsening of symptoms at follow up. In contrast, 60% (15/25) of the treated symptomatic patients had complete resolution of symptoms and none had worsening of symptoms at follow up. Conclusion: Most symptomatic ACF-dAVFs present with hemorrhage. Cortical venous drainage is a key angio-architecture feature of ACF-dAVFs that accounts for their aggressive presentation. Microsurgery is more effective that other strategies for managing ACF-dAVFs. The analysis of this large cohort of ACF-dAVFs suggests that treatment is warranted at the time of diagnosis, independently of symptomatic status. Disclosures: S. Sanchez: None. A. Raghuram: None. L. Wendt: None. M. Hayakawa: None. C. Chen: None. J. Sheehan: None. L. Kim: None. I. Abecassis: None. M. Levitt: None. K. Jayaraman: None. R. Guniganti: None. A. Kansagra: None. G. Lanzino: None. E. Giordan: None. W. Brinjikji: None. D. Bulters: None. A. Durnford: None. C. Fox: None. A. Polifka: None. B. Gross: None. S. Amin-Hanjani: None. A. Alaraj: None. A. Kwasnicki: None. R. Starke: None. S. Sur: None. M. van Dijk: None. A. Potgieser: None. J. Satomi: None. Y. Tada: None. A. Abla: None. E. Winkler: None. R. Du: None. P. Rosalind Lai: None. G. Zipfel: None. C. Derdeyn: None. E. Samaniego: None.